Avenanthramide-C ameliorate doxorubicin-induced hepatotoxicity via modulating Akt/GSK-3β and Wnt-4/β-Catenin pathways in male rats - Alwaili, Maha Abdullah; Abu-Almakarem, Amal S.; Aljohani, Salwa; Alkhodair, Sahar Abdulrahman; Al-Bazi, Maha M.; Eid, Thamir M.; Alamri, Jehan; Mobasher, Maysa A.; Algarzae, Norah K.; A. Khayyat, Arwa Ishaq; Alshaygy, Luluah Saleh; El-Said, Karim Samy (Frontiers in Molecular Biosciences, 2024)
BackgroundDoxorubicin (DOX) drugs used in cancer treatment can cause various adverse effects, including hepatotoxicity. Natural-derived constituents have shown promising effects in alleviating chemotherapy-induced toxicities. This study addressed the effect of Avenanthramides-C (AVN-C) treatment in rats with DOX-indued hepatotoxicity.MethodsAutoDock Vina was used for the molecular docking investigations. In silico toxicity prediction for AVN-C and DOX was performed using the Pro Tox-III server. Four groups of ten male Sprague-Dawley rats were created: Group 1 (Gp1) served as a negative control, Gp2 received an intraperitoneal (i.p.) injection of AVN-C (10 mg/kg), Gp3 received an i.p. dose of DOX (4 mg/kg) weekly for a month, and Gp4 received the same dose of DOX as G3 and AVN-C as G2. Histopathological, molecular, and biochemical analyses were conducted 1 month later.ResultsThe study showed that treatment with AVN-C significantly ameliorated DOX-induced hepatotoxicity in rats by restoring biochemical alterations, boosting antioxidant activity, reducing inflammation, and modulating the Akt/GSK-3β and Wnt-4/β-Catenin signaling pathways in male rats.ConclusionThis study is the first to demonstrate the therapeutic effects of AVN-C therapy on DOX-induced liver damage in male rats. Therefore, AVN-C could have a pronounced palliative effect on the hepatotoxicity caused by DOX treatment. These findings suggest that AVN-C could potentially alleviate the hepatotoxicity associated with DOX-based chemotherapy.